Galaxywi laptop charger - Wong, Yee Mun; Sim, Ji Wei; Yeoh, Charissa Tian Ern; Loh, Ying Fei (2025)
This business plan introduces GalaxyWi, an innovative wireless laptop charger, designed to meet the increasing demand for portable, efficient and cable-free charging solutions. GalaxyWi offers a high-value proposition in the growing landscape of mobile computing accessories. As laptops continue to evolve toward minimalistic designs, the product responds to users’ desire for enhanced mobility, workspace organisation and technological sophistication. Our proposed business model integrates the design, manufacturing and assembly of key components, such as wireless transmitters, converters, adapters and receivers into a slim, lightweight, and user-friendly device. A distinctive feature of GalaxyWi is its customisation service, enabling customers to personalise the product with names, which elevates brand engagement and appeals to individual consumer identities. The device supports mainstream laptop brands, also in fulfilling a gap in the current wireless charging market. Targeting higher education group of people, and freelancers, GalaxyWi will be distributed through online platforms and roadshows. Our phased marketing strategy spans from brand awareness to advocacy, incorporating digital engagement, influencer collaborations, and retail displays. Financial projections estimate steady revenue growth, underpinned by effective cost management, a lean workforce, and a focus on scalability. inFit Sdn. Bhd. operates with a a single floor structure, manufacturing, stock storage, and logistics, as well as to accommodate executive offices, a discussion room, pantry, and other administrative functions. This layout reflects our emphasis on operational efficiency and cross-department collaboration. With a dedicated founding team, cost-conscious operations and a scalable business model, inFit Sdn. Bhd. is well-positioned to lead the wireless charging market segment with GalaxyWi.